Pengaruh Rasio Profitabilitas, Likuiditas Dan Leverage Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Sub Sektor Telekomunikasi Yang Terdaftar di Bursa Efek Indonesia Pada Periode 2018-2023) - Vachriyanti, Asma’ul Noer; Mardani, Ronny Malavia; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of profitability, liquidity and leverage ratios on firm value in Telecommunication sub-sector companies listed on the Indonesia Stock Exchange (BEI). This data source uses secondary data in the form of financial statements from each company from 2018-2023. The population used was 18 companies. The sample obtained was 10 telecommunication companies that had been selected by purposive sampling method. The analysis method used is multiple linear regression analysis using the SPSS Statistics for Windows 25 application. The results showed that profitability, liquidity and leverage ratios simultaneously had an effect on company value. profitability (return on assets), liquidity (current ratio) and leverage (debt to equity ratio) partially have a positive and significant effect on company value. Keywords : Company Value, Profitability, Liquidity, Leverage, Telecommunication